Pengaruh Model Pembelajaran Read, Answer, Discuss, Explain, Create (RADEC) Terhadap Literasi Sains Siswa Kelas V Sekolah Dasar Pada Materi Ekosistem - Purnomo, Ridwan Adi; Irianti, Mustika; Kumalasari, Lina (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2026)
Scientific literacy is an essential competence that elementary school students must possess to face the challenges of the 21st century. However, Indonesian students’ scientific literacy remains relatively low. One effort to improve scientific literacy is through the implementation of the Read, Answer, Discuss, Explain, and Create (RADEC) learning model. This study aimed to determine the effect of the RADEC learning model on fifth-grade students’ scientific literacy in ecosystem materials. This study employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The subjects were 30 fifth-grade elementary school students. Data were collected using a scientific literacy test administered before and after the implementation of the RADEC learning model. Data analysis techniques included normality tests, reliability tests, and paired sample t-tests using SPSS. The results showed an increase in students’ scientific literacy scores after the implementation of the RADEC learning model. The paired sample t-test results indicated a significance value of less than 0.05, indicating that the RADEC learning model had a significant effect on students’ scientific literacy in ecosystem learning.